2015
DOI: 10.1371/journal.pone.0117282
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin (IL)-15 as a Biomarker of Alzheimer's Disease

Abstract: Interleukin (IL-15), a pro-inflammatory cytokine has been studied as a possible marker of Alzheimer’s disease (AD); however its exact role in neuro-inflammation or the pathogenesis AD is not well understood yet. A Multiple Indicators Multiple Causes (MIMIC) approach was used to examine the relationship between serum IL-15 levels and AD in a well characterized AD cohort, the Texas Alzheimer's Research and Care Consortium (TARCC). Instead of categorical diagnoses, we used two latent construct d (for dementia) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 79 publications
3
21
0
Order By: Relevance
“…IL‐15 is a cytokine that induces the proliferation of NK cells and is up‐regulated in the presence of a viral infection. It is also known to reduce disease activity in celiac disease and has been implicated as a potential biomarker for Alzheimer's disease . Serum levels of IL‐15 in SLE patients have been examined previously , but the sample sizes of those studies were too limited for findings to be considered conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐15 is a cytokine that induces the proliferation of NK cells and is up‐regulated in the presence of a viral infection. It is also known to reduce disease activity in celiac disease and has been implicated as a potential biomarker for Alzheimer's disease . Serum levels of IL‐15 in SLE patients have been examined previously , but the sample sizes of those studies were too limited for findings to be considered conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic infection in AD was also associated with a reduction in several pro-inflammatory cytokines, mainly associated with the adaptive immune system. The few studies that have examined their role in AD have found: (i) elevated serum IL7 in early to mild AD [ 20 ]; (ii) elevated IL12p40 levels in the cerebrospinal fluid (CSF) of Alzheimer’s patients [ 68 ]; (iii) administration of IL12p40 subunit blocker enhanced microglial phagocytosis and reduced inflammation in Aβ transgenic mice [ 68 ]; (iv) raised IL15 levels in the CSF and serum of Alzheimer’s patients correlated with severity of cognitive dysfunction [ 6 , 58 ]; (v) increased peripheral IL16 in AD [ 19 ]; and overexpression of IL17A decreased soluble Aβ levels without exacerbating neuroinflammation in a mouse model of Aβ accumulation [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TARCC's model, constrained across random 50% splits, had acceptable fit (chi square 5 1264. 6 [295], P , .001; CFI 5 0.95; RMSEA 5 0.031) ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%